Controlling a Delivery Robot Based on Color Using Fuzzy Logic Method - Sapriyanto, Hidayat; Rasyad, Sabilal; Damsi, Faisal (Internet of Things and Artificial Intelligence Journal, 2025)
This research presents the design and implementation of an IoT-based delivery robot equipped with a line navigation system and color classification using Mamdani fuzzy logic. The robot follows a black line using infrared sensors and identifies delivery zones via color markers (red, green, blue, yellow) detected by a TCS3200 sensor. Fuzzy logic processes RGB input to classify colors and trigger item placement using a servo mechanism. The system integrates hardware components such as Arduino Mega, ESP8266, and L298N motor drivers, and utilizes the Blynk application for remote control. Navigation decisions are enhanced through fuzzy inference, enabling adaptation to sensor uncertainty and lighting variations. Experimental results show a 94% success rate in path following, 92% color classification accuracy, and sub-2-second response time for remote commands. The combination of fuzzy logic and IoT enables flexible, real-time control, making the system suitable for dynamic indoor environments like offices or labs.